2018
DOI: 10.1007/s11284-018-1606-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal hyperaccumulating Brassicaceae from the ultramafic area of Yahyalı in Kayseri province, Turkey

Abstract: Many of the plants found in serpentine areas are endemics and they may accumulate Ni at high concentration. High accumulation of Cr is rare, or in some views, never properly demonstrated. Generally, a very small proportion of any serpentine flora shows high accumulation of Ni, in some serpentine areas Ni accumulators are completely absent. There are approximately 570 hyperaccumulator plant species found on earth, 450 of them are Ni hyperaccumulators. A few of the Ni accumulators have potential for phytoremedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to these studies, no plant species with Cd, Cu and Zn hyperaccumulator properties were found in Turkey. (Reeves, 1988;Reeves et al, 1983Reeves et al, , 2001Reeves et al, , 2009Reeves andAdıgüzel, 2004, 2008;Adıgüzel and Reeves, 2012;Altınözlü et al, 2012;Aksoy et al, 2015;Çelik et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these studies, no plant species with Cd, Cu and Zn hyperaccumulator properties were found in Turkey. (Reeves, 1988;Reeves et al, 1983Reeves et al, , 2001Reeves et al, , 2009Reeves andAdıgüzel, 2004, 2008;Adıgüzel and Reeves, 2012;Altınözlü et al, 2012;Aksoy et al, 2015;Çelik et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been carried out about serpentine areas in Turkey. Until now, 55 serpentine areas have been examined in Turkey and 62 Ni-accumulators and more than 43 serpentine-endemics have been reported from these areas (Reeves, 1998;Reeves et al, 1983Reeves et al, , 2001Reeves et al, , 2009Reeves andAdıgüzel, 2004, 2008;Adıgüzel and Reeves, 2012;Altınözlü et al, 2012;Aksoy et al, 2015;Çelik et al, 2018). According to the Flora of Turkey, it is reported that there are 248 plants specific to serpentine areas, of which 119 are serpentinophytes and 129 are serpentinophages (Kurt et al, 2013;Özdeniz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As this mechanism requires concentration or accumulation rather than breakdown, this strategy involves the plant roots extracting inorganic pollutants from soil and water and translocating them to the plant shoots, followed by plant harvest for disposal or recycling. Silver, cadmium, cobalt, chromium, copper, mercury, manganese, molybdenum, nickel, lead, and zinc, as well as metalloids such as arsenic and selenium, can all be remediated (Bani et al, 2010;Zhang et al, 2010;Zhang et al, 2011;Yang et al, 2017;Çelik et al, 2018;Siraj et al, 2022).…”
Section: Phytoaccumulationmentioning
confidence: 99%
“…plants are known to accumulate metals in non‐glandular trichomes (Salt et al 1995, Iwasaki and Matsumura 1999, Küpper et al 2000, Lavid et al 2001a, Broadhurst et al 2004). Brassicaceae is known to have many identified heavy metal hyperaccumulators, including species of Arabidopsis , Alyssum , Brassica , Noccaea , Thlaspi , Streptanthus , Odontarrhena , Isatis , Microthlaspi and Pseudosempervivum (Peer et al 2003, Dar et al 2015, Çelik et al 2018). Thlaspi caerulescens Félix de Pallières has been assessed using forward and reverse genetic screens using T‐DNA insertional mutagenesis an is a model hyperaccumulator.…”
Section: Heavy Metal Accumulation and Detoxification In Plant Trichomesmentioning
confidence: 99%
“…Plants display one or a combination of different functional mechanisms of resistance towards the heavy metals. Accumulation in the aerial parts or roots and stabilized complex formation in the rhizosphere prevents leaching, volatilization and degradation (Lone et al 2008, Dar et al 2015, Emamverdian et al 2015, Çelik et al 2018). Plants belonging to Solanaceae, Chenopodiaceae, Brassicaceae and Asteraceae are metal accumulators (Thiebeauld et al 2005).…”
Section: Introductionmentioning
confidence: 99%